Potentially simple score of late gadolinium enhancement cardiac MR in acute myocarditis outcome. Issue 6 (1st December 2013) - Barone‐Rochette, Gilles; Augier, Caroline; Rodière, Mathieu; Quesada, Jean‐Louis; Foote, Alison; Bouvaist, Hélène; Marlière, Stéphanie; Fagret, Daniel; Baguet, Jean Philippe; Vanzetto, Gérald
<x xml:space="preserve">Abstract</x> Purpose To determine the value of cardiac MRI for the monitoring and the prognosis of patients with acute myocarditis. Cardiac MRI plays an increasingly important role in the diagnosis of acute myocarditis. However, it is less established as a prognostic tool, which requires specific postprocessing of images. Materials and Methods In a prospective pilot study, we assessed the prognostic value of the evolution in a simplified visual quantitative score (SQS) of late gadolinium enhancement (LGE) between initial hospitalization and 3 months later. The prognostic value was assessed at 1 year using a combination of death, heart transplant, and confirmed recurrence as main outcome. Results Twenty‐eight patients were included in this study. A significant correlation was found between LGE measured by SQS and planimetry (r = 0.95, P < 0.001). Intraobserver and interobserver reproducibilities were good for SQS (ICC = 0.95 [95% CI: 0.86 to 0.98], and 0.94 [95% CI: 0.84 to 0.98], respectively). At initial hospitalization, patient characteristics between the two groups were similar. Patients with stable or increased SQS suffered more frequently from clinical outcome events than patients with a decrease in SQS (P = 0.02). Conclusion Monitoring of the evolution of LGE using a simple visual score is of interest to identify patients at risk of pejorative prognosis after acute myocarditis. J. Magn. Reson. Imaging 2014;40:1347–1354. © 2013 Wiley Periodicals, Inc.